2011
DOI: 10.1002/ijc.26259
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation and growth inhibitory role of FHL1 in lung cancer

Abstract: Four and a half Lin-11, Isl-1, Mac-3 (LIM) protein 1 (FHL1) has been linked to carcinogenesis. However, the role of FHL1 in lung cancer remains unclear and the detailed mechanism underlying its tumor suppressive role is poorly understood. The purpose of this study was to examine FHL1 expression in lung cancer patients and to investigate how it was associated with lung cancer cell growth. Immunoblotting and immunohistochemistry showed that FHL1 protein was downregulated in over 90% of 80 lung cancer patients. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
57
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 32 publications
10
57
0
Order By: Relevance
“…FHL1 has a tumor suppressive role in a number of types of human cancer (7)(8)(9)12). The findings of the present study reveal that EZH2 may act as a regulator of FHL1 expression in human liver cancer.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…FHL1 has a tumor suppressive role in a number of types of human cancer (7)(8)(9)12). The findings of the present study reveal that EZH2 may act as a regulator of FHL1 expression in human liver cancer.…”
Section: Discussionsupporting
confidence: 51%
“…Notably, FHL1 as tumor suppressor gene on chromosome X has a high risk to be affected as a single hit of genetic and/or epigenetic abnormality on only one active allele could lead to complete inactivation of FHL1 (11). FHL1 exerts a tumor suppressor effect via multiple mechanisms, including the activation of the transforming growth factor-β-like and mitogen-activated protein kinase signaling pathways and protein interaction with zonula occludens-1, hypoxia-inducible factor 1-α and estrogen receptor α (7,9,12,13). However, the role of FHL1 in liver cancer has not been revealed and the mechanisms associated with FHL1 downregulation remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, FHL1 has been demonstrated to be important in carcinogenesis. FHL1 expression is downregulated in various types of malignancy, including breast cancer, liver cancer, kidney cancer, prostate cancer, gastric cancer, lung cancer and oral squamous cell carcinoma (OSCC) (8)(9)(10)(11)(12)(13). FHL1 exerts its tumor suppressive role via multiple mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…FHL1 activates the tumor suppressor gene p21 (WAF1/CIP1) and represses the oncogene c-myc through interaction with Smad2, Smad3 and Smad4 in liver cancer cells (10). In breast cancer cells, FHL1 interacted with estrogen receptors and thus decreases the expression of pS2 and cathepsin D, two estrogen-responsive genes (9 kinase (CDK) inhibitors p21 and p27 (Kip1) (12). Although it has been reported that FHL1 expression is downregulated in OSCC, including TSCC (13), the biological function and the underlying molecular mechanisms of FHL1 in TSCC remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…130 Fhl1 downregulation has been observed in several human cancers, including astrocytoma, mammary carcinoma, renal carcinoma, prostatic carcinoma, melanoma, hepatocarcinoma, pulmonary adenocarcinoma, and gastric cancer. 41,130,[132][133][134][135] Accordingly, low expression of Fhl1 correlates with deep tumor invasion of the serosal layer in patients with primary gastric cancer. 133 Taken together, these data indicate that Src uses Cas to inhibit Fhl1 expression to promote tumor cell growth and migration, and this process is reversed by contact normalization.…”
Section: Src Contact Normalization and Novel Tumor Suppressorsmentioning
confidence: 99%